2015
DOI: 10.1002/adem.201500269
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior and Mechanical Properties of Ultrafine‐Grained Pure Copper with Potential as a Biomaterial

Abstract: This study aims to evaluate and compare the mechanical and corrosion resistance properties of ultrafine-grained (UFG) copper with that of coarse-grained (CG) copper microstructures. Ultrafinegrained microstructures are produced through severe plastic deformation using rotary swaging. Potentiodynamic polarization and electrochemical impedance tests are performed at 37 C in Hank's solution as the simulated body fluid. The results reveal that the highly deformed UFG-materials not only show marked enhancement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…The observed corrosion products composition through EDS analysis is consistent with published finding on the degradation products of Zn alloys, hence, the possible corrosion products on Zn are ZnO, Zn(OH) 2 , Zn 3 (PO 4 ) 2 , Ca 3 (PO 4 ) 2 , and CaP [ 19 , 57 ]. In addition, the presence of Cu within the corrosion products of the Cu-containing alloys also suggest the dissolution of Cu from the alloy matrix, likely in the form of Cu 2 O [ [58] , [59] , [60] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed corrosion products composition through EDS analysis is consistent with published finding on the degradation products of Zn alloys, hence, the possible corrosion products on Zn are ZnO, Zn(OH) 2 , Zn 3 (PO 4 ) 2 , Ca 3 (PO 4 ) 2 , and CaP [ 19 , 57 ]. In addition, the presence of Cu within the corrosion products of the Cu-containing alloys also suggest the dissolution of Cu from the alloy matrix, likely in the form of Cu 2 O [ [58] , [59] , [60] ].…”
Section: Resultsmentioning
confidence: 99%
“…15 – b1, b2 . The corrosion of pure Cu in simulated physiological fluid were investigated in several studies [ 58 , 60 ], which is found to proceed via the following reactions: Oxide formation: 8Cu + 2H 2 O + O 2 → 4Cu 2 O + 4H + +4e − And oxide dissolution: Cu 2 O + 2H 2 O → 2Cu 2+ + H 2 O +2e − …”
Section: Discussionmentioning
confidence: 99%
“…The samples with lower corrosion current density, more positively corrosion potential shift and higher impedance had better corrosion resistance properties. 20,21 As Figure 4(a) shown, the impedance of MACP was the highest and the corrosion current was lowest. The MA had the highest corrosion potential but the lower impedance.…”
Section: The Corrosion Resistance Of the Samplesmentioning
confidence: 95%
“…V súčasnosti sú na materiály, ktoré sa využívajú v medicíne pri operačnej intervencii poškodených tkanív, kladené vysoké požiadavky najmä z pohľadu ich funkčnosti a biokompatibility [1]. Horčík a jeho zliatiny patria k perspektívnym biologicky odbúrateľným materiálom, ktoré podliehajú degradácii v prostredí in vivo za súčasnej pozitívnej odozvy organizmu na vzniknuté korózne produkty až do ich úplného odbúrania.…”
Section: úVodunclassified